Assessing tree species diversity and structure of mixed dipterocarp forest remnants in a fragmented landscape of north-western Borneo, Sarawak, Malaysia. (May 2020) - Ganivet, Elias; Unggang, Joanes; Bodos, Vilma; Demies, Malcom; Ling, Chea Yiing; Sang, Julia; Bloomberg, Mark
Highlights: High conservation value of the studied forest remnants in terms of tree diversity. Impacts of past logging activities outlined by forest structure and pioneer abundance. Studied communities likely to experience time-delayed shifts in species composition. Using 10 × 50 m plots provides estimates consistent with those from larger plots. Abstract: As forest fragmentation continues in many parts of the tropics, the conservation value of forest remnants remains controversial. Our study aimed to assess the structure and tree species diversity of mixed dipterocarp forest remnants from the Planted Forest Zone (PFZ) located in the Bintulu Division, Sarawak, compared with a forest considered relatively undisturbed (i.e. that has experienced no recent logging activities). We also compared three plot methods (50 × 50 m, 20 × 50 m and 10 × 50 m plots) in order to evaluate which could be used for time- and cost-effective inventories of structure and tree species diversity in fragmented forests. No significant differences were found between the fragmented forests and the relatively undisturbed forest for stem density, species richness and diversity indices (Shannon and Simpson). Dissimilarities in species, genus and family composition were observed between fragmented and relatively undisturbed forest, as well as between forest remnants themselves. These dissimilarities were likely to be related to intrinsic variation in these highly diverse tropical forests. However, an unusually high abundance of pioneer species (i.e. Macaranga ) was found in plots from forest remnants. The forest remnants also had significantly lower basal areas due to a lack of trees in large diameter classes, which is likely a result of impacts from past logging activities. Otherwise, our results highlight the current high conservation value of the forest remnants—although the studied communities are likely to experience time-delayed shifts in species composition and/or extinctions in the future, with the effect of fragmentation on biodiversity being currently underestimated. Finally, for further studies of fragmented forests we recommend the use of 10 × 50 m plots which are faster and easier to implement in the field while providing estimates of structure and tree species diversity that are consistent with those from larger plots.